CAM-DR: Mechanisms, Roles and Clinical Application in Tumors - Huang, Yuejiao; Wang, Yuchan; Tang, Jie; Qin, Shiyi; Shen, Xianjuan; He, Song; Ju, Shaoqing (Frontiers in Cell and Developmental Biology, 2021)
Despite the continuous improvement of various therapeutic techniques, the overall prognosis of tumors has been significantly improved, but malignant tumors in the middle and advanced stages still cannot be completely cured. It is now evident that cell adhesion-mediated resistance (CAM-DR) limits the success of cancer therapies and is a great obstacle to overcome in the clinic. The interactions between tumor cells and extracellular matrix (ECM) molecules or adjacent cells may play a significant role in initiating the intracellular signaling pathways that are associated with cell proliferation, survival upon binding to their ligands. Recent studies illustrate that these adhesion-related factors may contribute to the survival of cancer cells after chemotherapeutic therapy, advantageous to resistant cells to proliferate and develop multiple mechanisms of drug resistance. In this review, we focus on the molecular basis of these interactions and the main signal transduction pathways that are involved in the enhancement of the cancer cells' survival. Furthermore, therapies targeting interactions between cancer cells and their environment to enhance drug response or prevent the emergence of drug resistance will also be discussed.